DEVELOPMENT OF MUALLAF HELP APP AS CONVERT ‘s MEDIUM OF DATA STORAGE - Maisura, Mira; Sabaruddin, Muhammad; Muazzinah, Muazzinah (UIN Ar-Raniry, 2023)
This study aims to map the existence of converts in the city of Subulussalam. In essence, converts are expected to be able to participate in guidance activities from authorized institutions, as part of their spiritual journey. The existence of converts who are scattered and often not tracked by this institution is often neglected. Not only in terms of assistance but also social assistance. Social assistance itself is considered an important thing considering the number of cases of converts who are rejected by their families after converting to other religions. The Muallaf Help application is expected to be a tool that will map the location of the Muslim converts' residence, record their complete profile, help them to get good assistance and social assistance. All of these activities will take place under the supervision of the Subulussalam Muallaf Center. This converts application is designed with the waterfall development model as the formation and development. This system is also assisted by an analytical method that serves as an assessment to determine the extent to which this system can be accepted using the UTAUT approach.